Yield Performance of Mungbean Genotypes as Influenced by Herbicides with Different Weed Management Practices - Shams Shaila Islam (Green Engineering Society, 2020)
This research was conducted to investigate the effect of different herbicides with weed management practices on growth and yield performance of mungbean genotypes. The experiment consisted of two factors were mungbean genotypes and weed management. There were two genotypes namely BARI Mung 6 and BARI Mung 8. While there were five weed management practices namely control/no weeding and without herbicide application (T1), hand weeding at 20 and 40 DAS (T2), pre emergence herbicide (Panida) at 1-2 DAS (T3), pre emergence herbicide (Neon) at 2-3 DAS (T4), and post emergence herbicide (Neon) at 10-15 DAS+hand weeding (T5). The results revealed that BARI Mung 6 stand superior to BARI Mung 8 in respect of dry matter content/plant, pods/plant, seeds/plant, seed yield, and 1000 seed weight. Among weed management practices, maximum plant height (53.70 cm), dry matter weight/plant (17.96 g), pods/plant (18.31), seeds/plant (171.47), maximum weed control efficiency (33.78 %) obtained from T3 treatment. Based on the interaction effect showed that BARI Mung 6 weeded with pre emergence herbicide (Panida) at 1-2 DAS produced maximum seed yield (1.79 t/ha) as well as yield attributes showed 2.29 % higher seed yield.